Análisis de la actividad enzimática de hemicelulasas de dos razas de Colletotrichum lindemuthianum con diferentes sustratos naturales - Díaz Tapia, Karla Morelia (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Colletotrichum lindemuthianum is a phytopathogenic fungus that causes anthracnose in the common bean plant (Phaseolus vulgaris L.). Hemicellulases such as endo-β-1,4-xylanase (XYL), α-L-arabinofuranosidase (ABF), β-xylosidase (XYLO), and cellulases such as cellobiohydrolases (CBH) that secrete the fungus, participate in the degradation of the plant cell wall of its host. In this work, the mycelial growth and activity production of XYL, ABF, XYLO and CBH in two races of C. lindemuthianum with different lifestyle (0 non-pathogenic and 1472 pathogenic), in culture media supplemented with hypocotyls and bean bean, water lily (Eichhornia crassipes) and cane bagasse. The results showed that the water lily favors the greater production of mycelial biomass of the two races of C. lindemuthianum. However, race 1472 (pathogenic) showed better mycelial growth than race 0 (non-pathogenic). On the other hand, C. lindemuthianumno grows well in glucose or cellulose, prefers complex substrates rich in pectin and hemicellulose, suggesting a specialization in pectinolytic and hemicellulolytic activity. Regarding the secretion of enzymatic activity, in both fungi, the secretion of ABF activity occurs in the first nine days in all the substrates tested. It was found that both races of C. lindemuthianum had the highest activity of XYL in the middle with water lily. On the other hand, race 1472 (pathogen) of C. lindemuthianum had the highest activity of ABF, XYLO and CBH in the middle with water lily. However, the pattern of secretion of xylanolytic activity (XYL and XYLO) in middle with hypocotyls was differential between both races, rapid in race 0 (non-pathogenic) and delayed in race 1472 (pathogenic). Similarly, the cellulolytic activity (CBH) secretion pattern in all tested substrates was differential between both races, rapid in race 0 (non-pathogenic) and delayed in race 1472 (pathogenic).

Colletotrichum lindemuthianum es un hongo fitopatógeno que provoca antracnosis en la planta del frijol común (Phaseolus vulgaris L.). Hemicelulasas como la endo-β-1,4-xilanasa(XYL), α-L-arabinofuranosidasa (ABF), β-xilosidasa (XYLO), y celulasas como la celobiohidrolasas (CBH) que secreta el hongo, participan en la degradación de la pared celular vegetal de su hospedero. En este trabajo, se evaluó el crecimiento micelial y producción de actividad de XYL, ABF, XYLO y CBH en dos razas de C. lindemuthianum con diferente estilo de vida (0 no patógena y 1472 patógena), en medios de cultivo suplementados con hipocotilos y ejote de frijol, lirio acuático (Eichhornia crassipes) y bagazo de caña. Los resultados mostraron que el lirio acuático favorece la mayor producción de biomasa micelial de las dos razas de C. lindemuthianum. Sin embargo, la raza 1472(patógena) presentó mejor crecimiento micelial que la raza 0 (no patógena). Por otro lado, C. lindemuthianumno crece bien en glucosa o celulosa, prefiere sustratos complejos ricos en pectina y hemicelulosa, sugiriendo una especialización en actividad pectinolítica y hemicelulolítica. Respecto a la secreción de actividad enzimática, en ambos hongos, la secreción de actividad ABF ocurre en los primeros nueve días en todos los sustratos probados. Se encontró que ambas razas de C. lindemuthianum presentaron la mayor actividad de XYL en medio con lirio acuático. Por otro lado, la raza 1472 (patógena)de C. lindemuthianum presentó la mayor actividad de ABF, XYLO y CBH en medio con lirio acuático. Sin embargo, el patrón de secreción de actividad xilanolítica (XYL y XYLO) en medio con hipocotilos fue diferencial entre ambas razas, rápido en la raza 0 (no patógena) y retrasado en la raza 1472 (patógena).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FMVZ-R-M-2020-0318; Biotecnología pecuaria; Hemibiotrófico; Β-Xilosidas; Celobiohidrolasas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1968